Breast Reconstruction with the Free Bipedicled Inferior TRAM Flap by Anastomosis to the Proximal and Distal Ends of the Internal Mammary Vessels - Li, Senkai; Mu, Lanhua; Li, Yangquin; Xu, Jun; Yang, Mingyong; Zhao, Zhenmin; Liu, Yuanbo; Li, Junlai; Ling, Yichun (Journal of Reconstructive Microsurgery, 2002)
Breast reconstruction after traditional radical mastectomy is particularly challenging for the plastic surgeon. Not only the breast, but subclavian and anterior axillary-fold deformities need to be corrected. An entire TRAM flap (including zone IV) is required, and bipedicled deep inferior epigastric vessels are needed to insure that the entire flap will survive completely. However, on the chest, it is difficult to locate the two suitable sets of recipient vessels for the two pedicles. The thoracodorsal vessels have usually been damaged during axillary dissection or radiation therapy.In the past, the proximal ends of the internal mammary artery and vein (IMA, IMV) have been used as recipient vessels with free flaps, with ligation of the distal ends. These authors have used both the proximal and distal ends of the IMA and IMV as recipient vessels for end-to-end anastomoses to the bipedicled deep inferior epigastric vessels (DIEA, DIEV) in seven clinical cases, with very satisfactory results obtained.Anatomic studies of the IMA and IMV were done in 10 dogs and two active patients, including studying hemodynamic changes at the proximal and distal ends of the IMA, and evaluation of perfusion units in the free bilateral TRAM flap. In the animal experiments, the mean pressure at the distal ends was 86/77 mmHg (left sides) and 87/78 mmHg (right sides); pressure was 63 to 71 percent of the proximal ends (p<0.05). There was no statistically significant difference between the pressures on the left and right sides. In the two patients, and in 5 others, the pressure at the distal ends was 66 and 58 mmHg, which was 75 to 77% of the pressure at the proximal ends. The blood flow at the two anastomotic stomas was similar in a 5-year follow-up.The clinical and experimental studies showed that the distal IMA has reduced perfusion pressure, but that it provides excellent flow and flap perfusion, allowing reliable use of two pedicles for survival of the entire flap.
Keywords: Bipedicled inferior TRAM flap; anastomosis to proximal and distal ends of internal mammary vessels.